COORDINATE TRANSFORMATION FROM KARBALA 1979 AND WORLD GEODETIC SYSTEM 1984 TO IRAQI GEOSPATIAL REFERENCE SYSTEM - Y. Hussain, Ruba (Journal of Engineering and Sustainable Development, 2022)
Nowadays, the transformation between coordinate systems is the major interested problems especially in Iraq. There are many coordinate systems used to produce maps and documentations due to different datums and spheroids. These coordinate systems are preferable to be unified in local countries. Thus, this paper deals with the transformation of coordinate systems of Karbala 1979 Polservice and World Geodetic System (WGS) 1984 to Iraqi Geospatial Reference System (IGRS). Accurate and well distributed control points are selected to cover the study area in Baghdad city, Iraq. Coordinate transformations are implemented using ArcGIS application mainly. Also, MATLAB software is used to convert geographic to map coordinates and vice versa by designing two MATLAB programs. The differences between the coordinate systems have been calculated. The results found that the discrepancies between Karbala 1979 Polservice and IGRS are about 278.6 m, -287.6 m, 0.01 second, and -11.2 second in northing, easting, latitude, and longitude, respectively. The WGS 1984 is superposed to IGRS and the distinction between them is negligible. The map coordinate differences between ArcGIS and MATLAB results are about -16 to 14 mm in northing and about -13 to 12 mm in easting, while the latitude and longitude differences are zero.